A case report and literature review on ovarian lymphangioma - Yang, Fang; Zhu, Wenjing; Shan, Wenjun; Zhang, Yanping; Li, Ruilin; Wang, Wenyan (Frontiers in Oncology, 2024)
Ovarian tumors can be divided into epithelial tumors, germ cell tumors, sex cord-stromal tumors and metastatic tumors according to histological types. Their biological behaviors are different. Lymphangioma is a rare benign tumor that can occur anywhere in the body. Among them, ovarian lymphangioma is particularly rare. The case we reported is the case of ovarian lymphangioma. The patient was admitted to the hospital one month after the physical examination found the ovarian mass. After the examination, the patient was treated with laparoscopic surgery. The patient recovered well after the operation, and no recurrence was found after the follow-up.